Profile and Economic Impacts of Agriculture and Natural Resource Industries in the Suwannee River Basin Counties of Florida - Mohammad Rahmani; Alan W. Hodges; W. David Mulkey (EDIS)
This paper presents an analysis of the regional economic impacts of agriculture and natural resource industries in the Suwannee River Water Management District in north-central Florida. The report provides a profile of agriculture and natural resource industries and an overview of their economic impacts for the Suwannee River Basin region. The report is based on data from the IMPLAN Pro database for Florida counties for 2002 and data from the 2002 Census of Agriculture.